RESEARCH MANAGEMENT POLICY IN DEFENSE AND SECURITY - Susanti, Vita; Hartanto, Agus; Subekti, Ridwan Arief (Pusat Penelitian Perkembangan Iptek, LIPI, 2014)
As a sovereign nation, Indonesia has a strategy to defend itself against threats from outside and within the country. That requires a strong defense, both in terms of the number of military personnel and the number of defense equipment. So far, we have mostly the weaponry purchased and hung from abroad. This paper discusses the results of the study several policies and government regulations in defense and securi-ty in Indonesia. The methodology used is the start of data collection both primary data and secondary data, and from these data calculated the ideal number of military personnel and defense equipment. From the analysis of the data can be identified that one of the obstacles faced by Indonesian defense is the ratio of the number of military personnel to the personnel composition of the population as well as Army, Navy, and Air Force are still not ideal as well as the number of defense equipment owned is but below standard. In addition, the documents are not MP3EI clear roadmap on the development, engineering, and purchases of defense equipment and targets each year. Another problem is the absence of good coordination on defense research consortium activities. For that recommended the need for cooperation between military R & D, universities, and other research institutions under one umbrella defense research resulting in better research synergy.